A Novel Approach to Building a Heterogeneous Emergency Response Communication System - Janez Sterle; Miha Rugelj; Urban Sedlar; Luka Koršič; Andrej Kos; Peter Zidar; Mojca Volk (International Journal of Distributed Sensor Networks)
We present a specification and a nationwide pilot implementation of a future public safety communication system. We propose a novel approach to survivable heterogeneous emergency communication systems, merging professional and commercial off-the-shelf (COTS) equipment, communicating over state-of-the-art mobile and satellite links. We explain the architecture and functional outline of an Advanced Emergency Response Communications System (A-ERCS), which was developed and integrated with professional, commercial, and ad hoc networks to provide survivable communications services and sensor-based applications to support public safety agencies in their day-to-day operation and disaster relief missions. Further, we present the results of a real-world pilot implementation, customized for fire fighter services in Slovenia, and discuss the outcomes of performance tests, showing how the proposed solution can be applied in public safety practice and how COTS technologies can be efficiently and reliably reused in this specific domain.